THE INFLUENCE OF INTERNATIONAL LAW ON MUNICIPAL LEGAL SYSTEMS IN ASEAN - Regina Cyrilla Candra (President University, 2024)
The paper explores the influence of international law on ASEAN member states' municipal legal systems, with a focus on treaty incorporation, customary international law, and involvement with international jurisprudence and institutions. It emphasizes the challenges that ASEAN faces, such as fragmentation, a lack of public awareness, and varying political conditions, which interfere with unified implementation of international law. Despite these challenges, mutual dependence and aspirations for regional integration demands continuous compliance to international law. The ASEAN Charter plays an essential role in strengthening the region's legal framework. Furthermore, efforts to address fragmentation, raise public awareness, and increase stronger political commitment to international law are essential for an ASEAN region that is stable, honors human rights, and is fully integrratedKeywords: ASEAN, Compliance, International law,